The Transcription Factor FRA-1/AP-1 Controls Lipocalin-2 Expression and Inflammation in Sepsis Model - Cao, Shan; Schnelzer, Anne; Hannemann, Nicole; Schett, Georg; Soulat, Didier; Bozec, Aline (Frontiers in Immunology, 2021)
Sepsis is a life-threatening condition characterized by excessive inflammation in its early phase. This is followed by an aberrant resolution phase associated to a prolonged period of immune suppression that can ultimately lead to multiple organ dysfunctions. This immunosuppression can be mediated by the functional reprogramming of gene transcription in monocytes/macrophages in response to prolonged lipopolysaccharide (LPS) exposure. Surprisingly, there is no report on the role of AP-1 transcription factors in this reprogramming process. Herein, we used the endotoxin tolerance model on murine bone marrow-derived macrophages in which tolerant cells stimulated twice with LPS were compared to naïve cells stimulated once. Out of all AP-1 transcription factors tested, Fosl1 gene stood out because of its unique regulation in tolerized cells. Moreover, we could correlate FRA-1 expression to the expression of an essential anti-inflammatory molecule involved in sepsis response, Lipocalin 2 aka NGAL. Identical results were obtained in human PBMC following the endotoxin tolerance model. When using FRA-1 deficient macrophages, we could confirm that FRA-1 regulates NGAL expression during the tolerant state. Interestingly, ChIP-seq and ChIP-qPCR revealed the binding of FRA-1 on Lcn2 promoter after LPS stimulation in these cells. Finally, we used an in vivo septic model of consecutive injection of LPS, in which the second stimulation is performed before the resolution of inflammation, in wild type and FRA-1 deficient mice. NGAL secretion was elevated in lung, spleen and serum of wild type tolerant mice, whereas it was significantly lower in tolerant FRA-1 deficient mice. Moreover, an increased inflammatory state likely dependent of the low level of NGAL was observed in these FRA-1 deficient mice. This was characterized by an increase of neutrophil infiltration in lung and an increase of apoptotic follicular cells in spleen. This suggests that FRA-1 expression supports resolution of inflammation in this model. Collectively, our data indicate that FRA-1 is involved in myeloid cell tolerance responses by mediating the functional reprogramming of Lcn2 transcription in response to prolonged LPS exposure. In conclusion, FRA-1 may have a protective role in the tolerance response of sepsis through the regulation of NGAL, leading to resolution of inflammation.